Interpretation of Spiritual Life According to the “Imago Dei” - Pędrak, Anna (Teologia w Polsce, 2020)
This article is the result of theological research on the subject of life. The phenomenon of life is multifaceted, but often it cannot be defined because it is a mystery. The author of the article, based on the truth that man is a biological-psycho-spiritual unity, interprets these spheres in the key of St. Bonaventure’s idea, describes them as vestigium, umbra, and imago Dei. The issue of spiritual life in the category of Imago Dei is analyzed in detail. The author tries to answer the questions that arise by using not only theological fields: or is there an openness to transcendence only in a man? What does it mean to be an image of God? How to achieve a full life? The sphere of bios, psyche, and zoe in the human person are permeating each other, but this spiritual life transcends the previous two planes. This distinguishes man from other creatures and gives him a unique character. God, in His goodness and freedom, grants man life, creates him as a free being and in His image. But the perfect image of the Father is Jesus Christ. In His Incarnation, He showed us the fullness of humanity and through imitation and union with Christ, man can become conformed to the image of God. In this way, it is finally possible to obtain full participation in the communion with God in the Holy Trinity.